Exposure to early-life adversity and long-term trajectories of multimorbidity among older adults in China: analysis of longitudinal data from the China Health and Retirement Longitudinal Study - Xinyan Zhang; Huiying Liu; Mi Zhang; Xinyi Zhao (BMJ Open)
Objectives This study aimed to identify long-term distinct trajectories of multimorbidity with ageing from 50 to 85 years among Chinese older adults and examine the relationship between exposure to early-life adversity (ELA; including specific types of adversity and accumulation of different adversities) and these long-term multimorbidity trajectories.Design The group-based trajectory models identified long-term multimorbidity trajectories. Multinomial logistic regression models were used to examine the relationship between ELA and the identified multimorbidity trajectories.Setting This study used data from the China Health and Retirement Longitudinal Study (CHARLS, 2011–2018) and the 2014 Life History Survey.Participants We used data from 9112 respondents (aged 60 and above) of the 2018 wave of CHARLS.Outcome measures Each respondent’s history of chronic conditions and experiences of ELA were collected from the 2011–2018 waves of CHARLS and the 2014 Life History Survey.Results Four heterogeneous long-term trajectories of multimorbidity development were identified: ‘maintaining-low’ (19.1%), ‘low onset-rapidly increasing’ (23.3%), ‘middle onset-moderately increasing’ (41.5%) and ‘chronically-high’ (16.2%). Our findings indicated that the heterogeneity can be explained by ELA experiences. Across various types of different ELA experiences, exposure to food insufficiency (relative risk ratios from 1.372 (95% CI 1.190 to 1.582) to 1.780 (95% CI 1.472 to 2.152)) and parental quarrel/divorce (relative risk ratios from 1.181 (95% CI 1.000 to 1.394) to 1.262 (95% CI 1.038 to 1.536)) had the most prominent associations with health deterioration. The accumulation of more different ELA experiences was associated with a higher relative risk of developing more severe multimorbidity trajectories (relative risk ratio for five to seven ELAs and chronically high trajectory: 7.555, 95% CI 4.993 to 11.431).Conclusions There are heterogeneous long-term trajectories of multimorbidity in Chinese older adults, and the risk of multimorbidity associated with ELA accumulates over the lifespan. Our findings highlight the role of a supportive early-life family environment in promoting health development across the lifespan, advocating for the integration of life-course approaches to implementing health disparity interventions.